2018
DOI: 10.1177/0218492318799901
|View full text |Cite
|
Sign up to set email alerts
|

One more method for arterial cannulation in aortic arch surgery (“Penza cannulation”)

Abstract: Here we propose a new method of aortic cannulation in type A aortic dissection and aortic arch aneurysms. Aortic cannulation is performed through any of the ostia of brachiocephalic arteries and has been successfully used in 77 patients. This procedure is simple, safe, effective, and might be used as one of the alternatives to the classic methods of arterial cannulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Studies stress the importance of strategic cannulation in AAD repair, emphasizing the need for meticulous planning and execution. Due to their prospective benefits, techniques such as axillary cannulation and direct true lumen cannulation have gained attention [4] [5]. Not only does proper cannulation assure the safety of CPB, but it also influences postoperative outcomes.…”
Section: Review the Significance Of Appropriate Cannulation Technique...mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies stress the importance of strategic cannulation in AAD repair, emphasizing the need for meticulous planning and execution. Due to their prospective benefits, techniques such as axillary cannulation and direct true lumen cannulation have gained attention [4] [5]. Not only does proper cannulation assure the safety of CPB, but it also influences postoperative outcomes.…”
Section: Review the Significance Of Appropriate Cannulation Technique...mentioning
confidence: 99%
“…Subclavian/Axillary Artery Appropriate for cerebral perfusion, evades an aortic cannulation Unfavorable anatomy, risk of mal perfusion [5] Femoral Cannulation Used commonly, easily accessible Inadequate cerebral perfusion [42] Samurai…”
Section: Cannulation Site/technique Advantages Drawbacksmentioning
confidence: 99%
“…We put purse-string sutures on the base of the left subclavian artery (LSA) and cross-clamp it at the origin and 3 cm above the ostium and then transect the artery. Under visual control, we insert an arterial cannula through the LSA ostium into the true lumen of the proximal part of the descending aorta 1 ( Fig. 1A ).…”
Section: Technicsmentioning
confidence: 99%
“…Rosseykin et al (64) reported a new cannulation technique called "Penza cannulation." This is double artery perfusion, which included two steps: (I) the cannula was inserted into the true lumen of descending aorta via the left subclavian artery; and (II) the left subclavian artery, left CCA, and the brachiocephalic artery was replaced using a trifurcation graft with an added perfusion side-arm ("branch first" technique).…”
Section: Penza Cannulationmentioning
confidence: 99%